2022
DOI: 10.1111/1365-2435.14173
|View full text |Cite
|
Sign up to set email alerts
|

Phenological research based on natural history collections: Practical guidelines and a lepidopteran case study

Abstract: Natural history collections (NHCs) have been indispensable to understanding longer‐term trends of the timing of seasonal events. Massive‐scale digitization of specimens promises to further enable phenological research, especially the ability to move towards a deeper understanding of drivers of change and how trait–environment interactions shape phenological sensitivity. Despite the promise of NHCs to answer fundamental phenology questions, the use of these data resources presents unique and often overlooked ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 107 publications
0
33
0
Order By: Relevance
“…Recent work on plants (Li et al 31 ) and insects (Belitz et al 25 ) have shown that flowering and insect flight durations are longer in warmer areas in North America. Here we show that this general climate context matters less than unusual weather in determining many aspects of insect adult flight phenology.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent work on plants (Li et al 31 ) and insects (Belitz et al 25 ) have shown that flowering and insect flight durations are longer in warmer areas in North America. Here we show that this general climate context matters less than unusual weather in determining many aspects of insect adult flight phenology.…”
Section: Discussionmentioning
confidence: 99%
“…Here we use carefully curated phenometric estimates for Lepidoptera (moths and butterflies) of the Eastern USA generated from natural history collections (NHC) data. Lepidoptera are well-suited for phenology studies 24 , 25 , given that they have been well collected for centuries 26 , and have temperature-dependent developmental rates 27 . Recent work has also elucidated how key Lepidopteran life-history traits mediate phenological responses, providing a framework for further examining the importance of anomalous weather events.…”
Section: Introductionmentioning
confidence: 99%
“…Assembling key trait data and Fitting Phenology Models: We focus on two key traits that may impact phenological responses: overwintering stage and early versus late ight timing 42 . These two traits have been used in other studies and both have been shown to strongly relate to phenological responsiveness to both climate and landscape 42,43 . We determined the overwintering stage for mosquito species using literature resources (see Table 1 in Results).…”
Section: Methodsmentioning
confidence: 99%
“…the timing of biological events) in recent decades and centuries (Vitasse et al, 2022; Willis et al, 2017) in response to global change continues to accrue, and features in more than half a dozen papers in this Special Feature. Belitz et al (2023), in Functional Ecology , provide a framework and methodological checklist to address key questions in broad‐scale phenological patterns, using museum specimens on North American lepidopterans as a test case. Similarly, Dorian et al (2023) analysed 168 years of museum specimens and sighting data to assess phenological shifts for 70 species of solitary bees and found that, like many taxa, solitary bees have advanced their phenologies and lengthened their flight period.…”
Section: The Impacts Of Global Change On Phenologymentioning
confidence: 99%